Processes Behind Surfaces: Mobilities and Practices of the Danish OpenStreetMap Community - Stukanov,Kirill (2025)
This thesis investigates the practices and mobilities of the Danish OpenStreetMap community in order to understand how open-source mapping affects the problem-solving capacity. In more detail, my research challenges the perception of maps as ideal representations of the environment. Instead, it stresses the importance of mapping and the role of the mapper, who moves in a hybrid space, encountering and trying to solve different social problems. In this way, open-source mapping as a ‘bottom-up’ approach to digital mapping challenges the hegemony of commercial and official maps. As a case study, I examine the Danish local chapter of the OpenStreetMap community, which aims to create a free geographic database of the world. In terms of methods, this study uses digital ethnography, consisting of participant observations, semi-structured interviews and media go-along. First, participant observation helped me form initial ideas about practices within the community. Second, interviews allowed me to hear from the mappers’ perspective about what they do. Finally, media go-along deepened my understanding of how mappers move between devices and platforms. The theoretical framework of this study includes the new mobilities paradigm (Sheller & Urry, 2006), relational space (Massey, 1998) and hybrid space (de Souza e Silva, 2006). The findings show that members of the Danish OpenStreetMap community engage in a variety of mapping practices. Mappers combine different types of mapping, use various mapping platforms and devices, communicate with each other on a community forum, mailing lists and social media, as well as organise physical events such as meet-ups and conferences. In addition, mappers have a wide range of interests in mapping, from mapping street names to humanitarian mapping. It turns out that mappers are scattered throughout the OpenStreetMap ecosystem, moving between different practices along unique trajectories and with different purposes. However, they all coexist within the common logic of collaborative mapping. Unlike pre-digital representational cartography, which viewed movement as pathology and space as pre-existing, open-source mapping considers movement as life and space as emerging from social relations. Moreover, mappers are mobile figures who move in a hybrid space created by digital, location-based and mobile technologies. These movements of mappers are full of politics. In contrast to commercial and official maps, OpenStreetMap prioritises the needs, interests and (im)mobilities of people from different social groups. However, there are three internal tensions within the Danish OpenStreetMap community: social fragmentation, geographical distribution and gender issues. Resolving these tensions would contribute to the individual right to mobility and general mobility justice. In this sense, the community of mappers could become an example of a mobile commons. The thesis concludes that a useful approach to open-source mapping is based on dialectics rather than black-and-white binary thinking. Finally, digital open-source and grassroots projects have the capacity to solve important social problems.
Keywords: OpenStreetMap; open-source mapping; practice; mobility; digital ethnography; mobile commons; problem-solving capacity.